2002
DOI: 10.1042/bj20020829
|View full text |Cite
|
Sign up to set email alerts
|

A novel Rho GTPase-activating-protein interacts with Gem, a member of the Ras superfamily of GTPases

Abstract: Gem is a Ras-related protein whose expression is induced in several cell types upon activation by extracellular stimuli. With the aim of isolating the cellular partners of Gem that mediate its biological activity we performed a yeast two-hybrid screen and identified a novel protein of 970 amino acids, Gmip, that interacts with Gem through its N-terminal half, and presents a cysteine-rich domain followed by a Rho GTPase-activating protein (RhoGAP) domain in its C-terminal half. The RhoGAP domain of Gmip stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 38 publications
1
55
0
Order By: Relevance
“…Next, we studied the role of a downstream component of Gmip signalling. Gmip has a Rho-GAP activity 28 and regulates cell morphology in cultured fibroblasts by deactivating RhoA. Although several studies suggested that RhoA is crucial for neuronal migration in the embryonic cerebral cortex [31][32][33][34][35] , neither the spatio-temporal activation pattern of RhoA signalling in the migrating OB neurons nor its regulatory mechanisms has been demonstrated.…”
Section: Identification Of Gmip As a Girdin-interacting Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we studied the role of a downstream component of Gmip signalling. Gmip has a Rho-GAP activity 28 and regulates cell morphology in cultured fibroblasts by deactivating RhoA. Although several studies suggested that RhoA is crucial for neuronal migration in the embryonic cerebral cortex [31][32][33][34][35] , neither the spatio-temporal activation pattern of RhoA signalling in the migrating OB neurons nor its regulatory mechanisms has been demonstrated.…”
Section: Identification Of Gmip As a Girdin-interacting Proteinmentioning
confidence: 99%
“…In this study, we focused on one of the signal-transduction proteins, Gmip (Gem-interacting protein; Supplementary Fig. 1a), a Rho-GAP 28,29 .…”
Section: Identification Of Gmip As a Girdin-interacting Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to directly inhibiting ROK activity, recent yeast-two hybrid studies have identified a second Gem-mediated cytoskeletal regulatory cascade [60] which involves both the novel Gem-interacting protein Gmip [66] and the membrane cytoskeletal linker protein Ezrin [60] (Fig. 2).…”
Section: Rgk Regulation Of Cytoskeletal Dynamics: Modulation Of Rho-dmentioning
confidence: 99%
“…2). GTP-bound Gem binds to active Ezrin at the plasma membrane-cytoskeleton interface, and this complex appears to be required for both the recruitment and activation of Gmip, which functions as a RhoGAP [66]. The recruitment of Gmip to the cell surface leads to the localized inactivation of Rho signaling [60].…”
Section: Rgk Regulation Of Cytoskeletal Dynamics: Modulation Of Rho-dmentioning
confidence: 99%